2014
DOI: 10.1186/1471-2369-15-91
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid: association with rate of renal function decline and time until start of dialysis in incident pre-dialysis patients

Abstract: BackgroundIn patients with chronic kidney disease (CKD) hyperuricemia is common. Evidence that hyperuricemia might also play a causal role in vascular disease, hypertension and progression of CKD is accumulating. Therefore, we studied the association between baseline uric acid (UA) levels and the rate of decline in renal function and time until start of dialysis in pre-dialysis patients.MethodsData from the PREPARE-2 study were used. The PREPARE-2 study is an observational prospective cohort study including in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
1
15
1
4
Order By: Relevance
“…For instance, results from a large cohort of the Swedish Renal Registry showed neither the rate of estimated glomerular filtration rate (eGFR) decline nor rapid progression to end stage renal disease (ESRD) was associated with serum UA levels in patients with CKD stage 3 to 5 [10]. This finding is concordant with some recent observational studies of patients with a wide range of renal function at baseline in the U.S. [11], Taiwan [12], and Europe (Germany, Austria, south Tyrol, and Netherlands)[13, 14]. However, large heterogeneity in the definitions of CKD progression and analytic methods among these studies precluded a firm conclusion.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…For instance, results from a large cohort of the Swedish Renal Registry showed neither the rate of estimated glomerular filtration rate (eGFR) decline nor rapid progression to end stage renal disease (ESRD) was associated with serum UA levels in patients with CKD stage 3 to 5 [10]. This finding is concordant with some recent observational studies of patients with a wide range of renal function at baseline in the U.S. [11], Taiwan [12], and Europe (Germany, Austria, south Tyrol, and Netherlands)[13, 14]. However, large heterogeneity in the definitions of CKD progression and analytic methods among these studies precluded a firm conclusion.…”
Section: Introductionsupporting
confidence: 81%
“…Although some studies showed no association between hyperuricemia and the progression of CKD [1014], other studies found hyperuricemia may hasten the failing of renal function measured by eGFR or increase the risk of developing ESRD(Table 4) [3142]. Among 63,758 subjects with baseline eGFR ≥ 60 ml/min/1.73 m 2 , the subjects with hyperuricemia had an average annual decline of eGFR of 2.5 ± 9.5 mL/min/1.73 m 2 , that was almost twice faster than those of patients with normal uric acid levels [31].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, T2DM patients in Study‐B and Study‐C had relatively low cardiovascular risk, and the duration of follow‐up in Study‐C and Study‐D was relatively short, both of which may limit direct generalization to the recently published GLP‐1RA cardiovascular outcome trials. Interestingly, the association between UA levels and progression of diabetic kidney disease appears to be present only in healthier subjects, that is, those with earlier stages of chronic kidney disease (CKD), and seems to be lost in more advanced CKD . Sixth, the effects of lixisenatide were investigated in the postprandial state and an active comparator was used rather than placebo, which may have led to a more heterogeneous response and thus hampers direct comparison with other reported studies that were performed in the fasting state.…”
Section: Discussionmentioning
confidence: 99%
“…33 progression of diabetic kidney disease appears to be present only in healthier subjects, that is, those with earlier stages of chronic kidney disease (CKD), 46 and seems to be lost in more advanced CKD. 47,48 Sixth, the effects of lixisenatide were investigated in the postprandial state and an active comparator was used rather than placebo, which may have led to a more heterogeneous response and thus hampers direct comparison with other reported studies that were performed in the fasting state. Seventh, lixisenatide markedly slows the gastric emptying rate, 23 which could affect purine uptake in the postprandial state.…”
Section: Recent Landmark Cardiovascular Safety Trials Indicate That Gmentioning
confidence: 99%
“…Hyperuricemia is common in CKD patients, and the association between uric acid and worsening renal function is well established (35). Animal studies have shown that oxidative stress and endothelial dysfunction due to hyperuricemia cause renal damage (36).…”
Section: Discussionmentioning
confidence: 99%